WAR AND PROPAGANDA. THE FIGURE OF SANDINO ON PROPAGANDA POSTERS DURING THE STRUGGLE IN LAS SEGOVIAS - Astorga Sánchez , Leonardo (2025)
This article analyzes the main concepts used during the fight in Las Segovias, Nicaragua. To this end, it reviews and consults propaganda material produced between 1927 and 1933 by the US occupation forces, the Marine Corps, and the Army for the Defense of National Sovereignty, headed by Augusto César Sandino. It is suggested that concepts such as patriotism, rebellion, bandits, and traitors, among others, were fundamental when constructing a representation of the opposing political actors. The conceptual history and the history of ideas served as theoretical references for this work.